1992
DOI: 10.1161/01.cir.85.1.106
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous transluminal coronary angioplasty of chronic total occlusions. Primary success, restenosis, and long-term clinical follow-up.

Abstract: BACKGROUND Angioplasty of chronically totally occluded vessels has been associated with a success rate well below and restenosis rate well above that for angioplasty of stenosed segments. However, long-term clinical outcome after successful revascularization of a chronically totally occluded vessel has not been reported in detail. METHODS AND RESULTS Accordingly, data for 480 patients undergoing angioplasty for chronic total occlusion at Emory Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
132
3
5

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(145 citation statements)
references
References 14 publications
5
132
3
5
Order By: Relevance
“…Suero, et al 11) found a better 10-year survival rate in patients admitted with stable angina pectoris who had undergone successful PCI when compared to unsuccessful PCI (74% versus 65%, P = 0.002). Bell, et al 16) and Ivanhoe, et al 17) also reported similar results. The mortality benefit of PCI in CTO may be a result of an improved ejection fraction and improvements in both systolic and diastolic functions of myocardium.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Suero, et al 11) found a better 10-year survival rate in patients admitted with stable angina pectoris who had undergone successful PCI when compared to unsuccessful PCI (74% versus 65%, P = 0.002). Bell, et al 16) and Ivanhoe, et al 17) also reported similar results. The mortality benefit of PCI in CTO may be a result of an improved ejection fraction and improvements in both systolic and diastolic functions of myocardium.…”
Section: Discussionmentioning
confidence: 59%
“…In our study, the success rate was 68.0%, which is comparable to the 60-70% success rates reported in other studies. 17,18) The number attained in our study did not appear to represent the real success rate of PCI for CTO because there was a selection bias by the physicians with respect to the decision to perform PCI. For this reason, the success rate of PCI is estimated to be less than 68% when all CTOs are taken into consideration.…”
Section: Discussionmentioning
confidence: 86%
“…Until 2005, the success rates of operators experienced in conventional CTO percutaneous coronary intervention (PCI) techniques has remained unchanged (60-70%), which is considerably lower than the success rates in nonocclusive coronary artery disease (Ivanhoe et al, 1992). Many techniques and devices (wires, microcatheters) have been introduced into clinical practice to improve the effectiveness of CTO revascularisation (Sumitsuji et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…PCI of CTO results in symptomatic improvement, improved left ventricle function and reduction in adverse remodelling. In addition recanalization of CTO leads to long-term survival benefit and avoidance of bypass surgery (Melchior, Doriot et al 1987;Ivanhoe, Weintraub et al 1992;Chung, Nakamura et al 2003;Cheng, Selvanayagam et al 2008). The number of CTO interventions has risen gradually due to better operator experience, technical improvements, and newer procedural techniques (these include contra-lateral coronary injection, "parallel" wire techniques, subintimal tracking and re-entry (STAR), retrograde approach with control antegrade retrograde tracking (CART), reverse CART).…”
Section: Guidance For Chronic Total Occlusion (Cto) Interventionmentioning
confidence: 99%